Situações de ensino de Língua Portuguesa para surdos do Ensino Médio de uma escola inclusiva em Belém-PA - REUTER, Carla Andreza Correa (2025)
This Course Conclusion Paper approaches the Portuguese language teaching for the deaf in inclusive schools. Its objective is to describe aspects of Portuguese language learning for deaf users of Libras in inclusive high school classrooms of a state school in Belém and, more specifically, to relate the experiences of deaf secondary school students on Portuguese language learning in inclusive rooms. Moreover, to present experiences obtained in the reading of poetic text in the Portuguese Language class for deaf and hearing students. To do that, we proceeded methodologically by a qualitative descriptive research with a field research and, about the technical procedures, a case study. The locus was an inclusive school in Belém - Pa and the subjects were 2 (two) female deaf students using Libras who studied in that high school of this school and a PIBID (Programa Institucional de Bolsa de Iniciação à Docência) scholarship student, who is the author of this paper. As for the techniques of data collection, a questionnaire, with 6 (six) open questions, was applied and documentary research was used. The data analysis was, partly, content and, partly, descriptive. In addition, this paper was theoretically based on Quadros (1997), Pinto (2011), Plestsch (2009) and others. We verified that Libras is fundamental for a Portuguese language learning for the deaf, although it is not an aspect present in all Portuguese Language classes. Moreover, there are other relevant aspects concerning the teaching of the Portuguese language for the deaf, such as the use of technological resources and student’s background knowledge.